A Case Study: Principal Actions in Inclusive School Practices at Yashiro Elementary School - Nugraheni, Khoiri; Isawa, Shinzo; Aprilia, Imas Diana (Universitas Ahmad Dahlan, 2025)
The implementation of inclusive education in Japan’s elementary schools is increasingly urgent, as national reforms prioritize equitable learning environments for special educational needs (SEN). Despite the commitment, challenges remain in interpreting the policy in school practices. School principals play critical role in the transition from policy to practice. This study explores the effectiveness of inclusive educational practices at Yashiro Elementary School under the principal actions in executing inclusive school practices. Utilize a qualitative case study design, data were collected through semi-structured interview with school principal and classroom observation in inclusive and resources setting. Focusing on the implementation of the Multi-tiered System of Supports (MTSS), data analysis was conducted using thematic analysis, enabling the identification of recurring patterns and core theme with the qualitative data. The findings reveal that strategic leadership, knowledgeable hiring of specialized staff, and collaborative teaching approaches significantly enhance the learning experiences of special educational needs (SEN) students, ensuring their successful inclusion in mainstream educational settings.